Summative objective structured clinical examination as a reference of learners' need before entering their internship - Eddie Hsiang-Hua Lai; Jenny Zwei-Chieng Chang; Chen-Ying Wang; Yu-Chun Cheng; Shih-Li Tsai (Elsevier, 2018)
Background/purpose: Objective structured clinical examination (OSCE) has found increasingly wide use in the education of clinical dentistry in recent years. The objectives of this study were to find the predictability of OSCE in representing a student's actual ability in a clinical environment and to provide instructors with better ideas to guide an individual student in a certain field. Materials and methods: Thirty-one dentistry students' qualification OSCE scores were obtained after the conclusion of their dental clerkship in December 2014. The OSCE scores were compared with the various scores given by instructors from different departments during their internship a year later. The correlation was investigated between these two scores. Results: The scores of the first station of OSCE-explaining a treatment plan for the restoration of a missing tooth-were correlated with the scores of prosthodontics in the internship. The scores of the fourth station of OSCE-explaining to a mother regarding the obtainment of a radiograph of her child's tooth-were correlated with the scores of orthodontics. In addition, the total score of the six OSCE stations was correlated with the scores of orthodontics, oral surgery, and pediatric dentistry during dental internship. Conclusion: The results of clerkship qualification OSCE could provide instructors with insights into the needs of the students before their entering internship. Keywords: Clerkship, Internship, Objective structured clinical examination, Need assessment